Exploring the perspectives of audit committee members on mandatory audit firm rotation in a South African context - Thomson, Chelsea (College of Accounting, 2019)
This study examines the perspectives of experienced audit committee members on mandatory audit firm rotation (MAFR) in a South African context. This follows the recent initiatives by the Independent Regulatory Board of Auditors (IRBA) to make audit firm rotation compulsory in South Africa. Semi-structured, in-person interviews were conducted with audit committee members in South Africa to explore and contribute to the existing literature on audit committee member positions on MAFR. Twenty-two audit committee members were interviewed. Key discussion areas revolved around the regulator’s intended impact of MAFR in South Africa, including the promotion of auditor independence, the lowering of audit firm market concentration and acceleration of the rate of transformation in the South African audit industry. The findings show a general consensus among the audit committee members interviewed that MAFR will not achieve any of the objectives of the IRBA and that the members are predominantly in opposition of MAFR. Furthermore, the members proposed various arguments against MAFR, illustrating how the policy has limited benefits, if any, and will introduce many monetary and non-monetary costs into the audit industry, which could negatively impact the appeal of the audit industry. The vast majority of members held the view that the primary purpose of MAFR in South Africa is not to promote auditor independence, but is rather intended to address market concentration and transformation. However, the findings indicate that MAFR is believed to not be the best solution for these issues and, as such, further research and alternative measures should be sought by the regulator.